Problem Solving Videos sebagai Media Teknologi Asistif untuk Memfasilitasi Mahasiswa Tunarungu di Kelas Inklusif - Sugiman, Sugiman; Pujiastuti, Emi; Nisa', Ziyana Endah Khairun (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2022)
Beberapa Perguruan Tinggi sekarang ini membuka kesempatan bagi siswa disabilitas misalnya tunarungu untuk menjadi mahasiswa di kelas inklusif. Oleh karena itu, penulisan artikel ini bertujuan untuk membahas: (1) Cara memberikan peran kepada mahasiswa tunarungu di kelas insklusif agar dapat ikut berpartisipasi dalam kegiatan ilmiah berupa diskusi dalam kelompok kecil mahasiswa. (2) Cara menyediakan media teknologi asistif berupa problem solving videos untuk memfasilitasi mahasiswa tunarungu di kelas inklusif dalam diskusi ilmiah. Langkah untuk mencapai tujuan tersebut dilakukan dengan cara: (1) pelatihan dan pendampingan mahasiswa dalam berbahasa isyarat, (2) mixed method yang menggabungkan R & D dan pendekatan kualitatif. R & D untuk menemukan keabsahan media teknologi asistif berupa problem solving videos, sedangkan pendekatan kualitatif untuk mengungkap aspek tanggapan subjek penelitian terhadap pemakaian media teknologi asistif berupa problem solving videos. Hasil yang diperoleh adalah: (1) Setelah dilaksanakan pelatihan dan pendampingan dalam berbahasa isyarat pada semua mahasiswa di kelas inklusif, mahasiswa tunarungu dapat terlibat pada kegiatan diskusi pada materi perkuliahan. (2) Semua subjek penelitian memberikan tanggapan positif dan mendukung ketersediaan media teknologi asistif berupa problem solving videos untuk memfasilitasi mahasiswa tunarungu di kelas inklusif dalam melakukan diskusi ilmiah.Problem Solving Videos as Assistive Technology Media to Facilitate Deaf Students in Inclusive ClassAbstractSeveral universities currently open opportunities for students with disabilities, such as the deaf to become students in inclusive classes. Therefore, the purpose of this article is to discuss: (1) how to give roles for deaf students in the class to be able to participate in scientific activities as discussion in small student groups; (2) how to provide assistive technology which is the problem-solving videos to facilitate deaf students in scientific discussion in the inclusive class. To achieve the purposes carried out: (1) training and monitoring students in sign language, (2) mixing the method by combining R & D method and qualitative approaches. R & D to find the validity of assistive technology media in the form of problem solving videos, while the qualitative approach is to reveal aspects of research subjects' responses to the use of assistive technology media in the form of problem solving videos. The results from this research are: (1) After training and assistance in sign language have been carried out for all students in the inclusive class, deaf students can be involved in discussion activities on lecture material. (2) All research subjects gave positive responses and supported the availability of assistive technology media in the form of problem solving videos to facilitate students with hearing impairment in the inclusive class in scientific discussions.